Generation, use and sharing of digital sequence information in crop improvement. Submission to the Twelfth Meeting of the Ad Hoc Open-Ended Working Group to Enhance the Functioning of the Multilateral System: Policy Brief - Lopez Noriega, Isabel; Rouard, Mathieu; Halewood, Michael; Sackville-Hamilton, Ruaraidh; Chiarolla, Claudio (2024)
This policy brief was commissioned by the Co-chairs of the Working Group to Enhance the Functioning of the Multilateral System of Access and Benefit-sharing under the International Treaty on Plant Genetic Resources for Food and Agriculture (International Treaty), with the aim of informing international discussions on the sharing of benefits arising from the use of digital sequence information (DSI) in the agriculture sector. The document was prepared by the CGIAR Initiative on Genebanks and the Secretariat of the International Treaty. Digital sequence information is transforming research, conservation and breeding for sustainable agriculture and food security. This policy brief seeks to shed light on the benefits and challenges that the current information revolution is generating.